ANALISIS MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PADA JURUSAN AKUNTANSI PSDKU POLNEP DI KABUPATEN SANGGAU - Nia Pratiwi; Chornolius Hendreo; Ermina Toliang (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2023)
The Think Pair Share (TPS) learning model is one of the learning models that need to be used in the implementation of teaching and learning activities, because the Think Pair Share (TPS) model is designed to invite students to think about finding answers to a question from a concept through a group (in pairs). One of the problems faced in accounting learning is the low student accounting learning outcomes because lecturers always use the lecture method so there is less interaction. This study aims (1) to find out how to analyze the Think Pair Share (TPS) learning model to improve student learning outcomes in joint venture material for the fifth grade advanced financial accounting course majoring in accounting at PSDKU POLNEP in Sanggau district (2) to find out how student learning outcomes are accounting in the joint venture material for the fifth grade advanced financial accounting course majoring in accounting at PSDKU POLNEP in Sanggau district after analyzing the Think Pair Share (TPS) learning model. This type of research is Classroom Action Research. This research was conducted in 2 cycles, using pre-test and post-test cycles, second cycle using post-test. Sources of data obtained from lecturers and students. The data collection techniques by means of interviews, observation, and documentation.